Health Information Technologies in the Support System of New Fathers’ Postnatal Depression: Scoping Review - Weijie Wang; Erika Penney; Jaime Garcia (Interactive Journal of Medical Research, 2026)
Abstract Background Perinatal mental health issues are widely recognized as a significant public health concern; however, fathers remain underrecognized and underserved within perinatal care systems. Existing reviews have largely focused on mothers, infants, couples, or general paternal mental health interventions, leaving limited synthesis of technology-based and digitally delivered support relevant to paternal perinatal depression. Digital interventions, including SMS programs, online groups, web-based platforms, mobile health apps, and hybrid digital follow-up, may offer flexible ways of engaging fathers; however, their evidence base remains unclear. Objective This scoping review aimed to map the available evidence on technology-based, digitally delivered, and hybrid interventions relevant to paternal postnatal depression and paternal perinatal mental health. Specifically, it examined the types of evidence available; how interventions varied by delivery mode, methodology, and population; how interventions were characterized in terms of format and duration; and what outcomes had been measured across studies. Methods This review was conducted in accordance with the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) framework. A comprehensive search was conducted between February and April 2025 and updated in June 2026 across multidisciplinary electronic databases. Search terms covered 4 concepts: fathers or nonbirthing parents, perinatal mental health, digital or technology-based modalities, and intervention or evaluation purpose. Eligible studies were peer-reviewed English-language articles in which fathers, expectant fathers, new fathers, male partners, or nonbirthing parents were active participants, target users, or reported subgroups, and in which a digital, technology-based, or hybrid support strategy was described or evaluated. Data were charted and synthesized descriptively and comparatively. Results Six studies met the inclusion criteria. The evidence included a feasibility study of an SMS-based, father-specific program, randomized controlled trials of hybrid psychoeducational or paternal support interventions, a pilot randomized feasibility trial of an online cognitive behavioral therapy–based intervention for pregnant people and partners, a mixed methods online group intervention for new fathers, and a feasibility, acceptability, and usability study of a father-specific mobile health app. Delivery modes included SMS messaging, WhatsApp follow-up, online video, telephone follow-up, online groups, web-based intervention content, and mobile app features. Outcomes included depression, anxiety, stress, parenting stress, dyadic adjustment, marital quality, resilience, usability, acceptability, engagement, adherence, and qualitative user experience. Findings were most consistent for feasibility, acceptability, and engagement, while evidence for effectiveness in reducing paternal postnatal depression remained limited and mixed. Conclusions The current evidence base is small, heterogeneous, and preliminary. Digital interventions may offer acceptable ways to engage some fathers and partners during the perinatal period. However, there is insufficient evidence to draw firm conclusions about effectiveness, scalability, or suitability for fathers experiencing perinatal depression. Future research should prioritize father-specific, theory-informed, co-designed digital interventions using validated paternal outcomes, longer follow-up, transparent engagement reporting, and more diverse samples.